KEPENTINGAN INDONESIA TIDAK MERATIFIKASI MARITIME LABOUR CONVENTION (MLC) TAHUN 2006-2014 - Salmah Wati; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research discusses about the interests of Indonesia did not ratify the Maritime Labour Convention (MLC) in 2006-2014. International Labor Organization has established an international convention on seafarers. Based on the ILO survey that transport goods from one place to another, and from one country to another that is 90% done with the use of sea transport. Therefore, the ILO established a maritime labor convention to ensure the full protection of the rights of seafarers throughout the world.The author analyzes this case use descriptive qualitative methods that collects data and facts through some literature such as books, journals, and websites. The theory is use to analyze the interests of Indonesia did not ratify the Maritime Labour Convention (MLC) is a theory of foreign policy realism perspective and the concept of national interest.The results of this research shows there are interest of Indonesia did not ratify the Maritime Labour Convention are the political interests and economic interests. Political interests that conflict interests between the Ministry of Manpower and Transmigration Ministry of Transportation, while the economic interests unpreparedness national governments and ship owners to meet rights standards sailors, as well as an imminent government fears a domino effect in the economic sector.Keywords: interest, Ratification, Seafarers, and Maritime Labour Convention